Altitude training for improvements in sea level performance. Is the scientific evidence of benefit? - Wolski, L. A.; McKenzie, D. C.; Wenger, H. A. (Sports Medicine, 1996)
Altitude training invokes physiological changes that are very similar to those caused by endurance training, As a result, it has been incorporated in the training regimes of elite athletes in an effort to improve sea level performance. Several training strategies, such as constant altitude exposure, intermittent altitude exposure or 'live high train low', have been used in an effort to incur an advantage in sea level performance over just sea level training alone. In spite of the accumulating scientific evidence that altitude training affords no advantage over sea level training, many coaches and athletes believe that it can enhance sea level performance for any athlete, whether endurance or power is the focus in their particular sport. However, altitude training may not be suitable for some athletes depending on their age, fitness level, health, iron status and the energy and technical requirements of their sport. The issue of whether altitude training enhances sea level performance remains a controversial topic.